Brand Image for Professional Services Firms in South Africa - Ramdhani, Suveer (My University, 2011)
In today‟s competitive marketplace, marketing activities are used to influence the buyer‟s perception of a professional services firm and therefore the brand image. To compete, professional services firms could leverage intangible assets such as brand image to improve perceptions, create differentiation and positively influence the procurement process. The purpose of this research was to explore which of the marketing activities as specified in the literature are most effective in influencing client perceptions of the brand, or brand image, a driver of brand equity, for professional services firms. The research first evaluated the relative importance of brand among criteria used when procuring professional services and then identified which marketing activities were perceived as most effective for developing the brand image of professional services firms. The research method employed in this study was qualitative in nature and utilised in-depth interviews of 12 senior executives of major businesses based in Johannesburg. The study revealed that brand is considered among the most important criteria when purchasing professional services only when the client requires a professional services firm to complete an assignment that incorporates a high level of interaction or results in a high level of interaction with key stakeholders. However, direct relationships and direct experience could easily engender the same level of trust if the professional services firm has adequate opportunity to engage with key stakeholders through appropriate marketing activities. The most effective marketing communication activities for developing the brand image of professional services are those that provide a degree of direct experience. The research found that marketing activities that provided a focused personal experience were recommended and were also more likely to have higher levels of participation. For emerging professional services firms, a focused approach to a specific segment of client firms in an industry, using marketing activities that provide select client staff with an experience of the professional services firm, is likely to yield favourable results
MBA - WBS
Keywords: Brand image; Professional firms